Effects of gamma radiation on the quality of Hass avocado fruits (Persea americana Mill.) (2022)
The Hass avocado is a crop with significant growth potential for Colombia as an export product; however, the country has reported quarantine-type pest insect species that limit its export. The objective of this research was to evaluate gamma radiation treatments of fruit in order to study its use as a post-harvest treatment. Gamma radiation levels were evaluated at 100, 200, 400 and 800 Gy and compared against a control without irradiation. The harvest maturity status was established as a blocking factor. The evaluation was carried out for 20 days after the application of the treatments, emulating conditions of refrigerated transport at 7 °C. The variables firmness, exocarp and mesocarp color, soluble solids, dry mass, respiration, and weight loss were analyzed longitudinally at five evaluation points, where time acted as an intrasubject factor in the analysis of longitudinal multivariate variance. The variables lipid peroxidation and ethylene production rate were evaluated only once at the end of the test. We found that the highest radiation treatment affected the color of the exocarp and the content of total soluble solids, while all treatments affected the respiratory intensity, increased lipid peroxidation, altering the color of the mesocarp, which is the tissue of greater commercial interest for fresh fruits. All the treatments affected the visual quality of the fruits independent of the point of harvest maturity.